Effect Of Teams Games Tournament (TGT) Cooperative Learning and Quartet Card Media on Elementary Students’ IPAS Learning Outcomes - Any Widayati; Ninik Indawati; Ari Brihandhono (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aimed to analyze the effect of the Cooperative Learning model of the Teams Games Tournament (TGT) type and the use of quartet card media on the learning outcomes of fourth-grade students in science (IPAS) subjects, both partially and simultaneously. This study used a quantitative approach with a quasi-experimental design. The study population included all fourth-grade students of SD Negeri Gugus 01, Panggungrejo District, in the 2025/2026 academic year, totaling 120 students, with a sampling technique using total sampling. The experimental group consisted of 60 students who received treatment with the TGT model assisted by quartet card media, and the control group consisted of 60 students who received conventional learning. The data collection instrument was an IPAS learning outcome test that had been tested for validity (r 0.361) and reliability (KR-20 = 0.901). Data analysis techniques used inferential statistical tests, including normality tests, homogeneity tests, linear regression tests, and hypothesis tests with the help of SPSS 25. The results showed that (1) the TGT learning model had a significant effect on science learning outcomes with a regression coefficient of 1.546 and a significance value of 0.000 (0.05); (2) the use of quartet card media had a significant effect on science learning outcomes with a regression coefficient of 0.370 and a significance value of 0.000 (0.05); (3) simultaneously, the TGT learning model and the use of quartet card media had a significant effect on science learning outcomes with a calculated F value of 48.674 (p=0.000) and a coefficient of determination (R²) of 0.631, which means that both variables contributed 63.1% to science learning outcomes. The findings of this study prove that the application of a game-based cooperative learning model supported by interesting learning media can increase student involvement and science-learning outcomes. Therefore, the TGT learning model assisted by quartet card media is recommended as an alternative science learning strategy for elementary schools.